ChemInform Abstract: Copper‐Catalyzed Desymmetric Intramolecular Ullmann C—N Coupling: An Enantioselective Preparation of Indolines. Issue 9 (5th March 2013) - Zhou, Fengtao; Guo, Jiajia; Liu, Jianguang; Ding, Ke; Yu, Shouyun; Cai, Qian
Abstract The first highly enantioselective protocol for preparation of indolines and tetrahydroquinolines via Cu‐catalyzed asymmetric desymmetrization of 2‐propanamines and 3‐pentaneamines, respectively is presented.